Vida Saludable: Sitios Web Confiables - Linda B. Bobroff; Leigh Ann Martin (EDIS, 2007)
Revised! FCS-8587-Span, a 3-page fact sheet by Linda Bobroff and Leigh Ann Martin, is the Spanish version of "Healthy Living: Reliable Web Sites" (FCS8587). It will help consumers understand how to identify reliable and trustworthy health-related web sites and lists a number of web resources. Revised to include and update links. Published by the UF Department of Family, Youth and Community Sciences, May 2007.